Analisis Dan Perancangan Sistem Informasi Retribusi Pasar Tradisional Kabupaten Gresik - Dimas Firjatullah Tsani; Henny Dwi Bhakti (Fakultas Teknik Universitas Cenderawasih, 2023)
Currently, various industries see the increasingly rapid development of modern technology, almost all institutions need a government information system, one of which is to automate data storage more quickly and easily. The levy receipt system is an example of information technology. One of the government agencies in Gresik Regency that has not implemented an information system for data processing is the Cooperative Service, located in Gresik, Kembangan, KEC.kebomas, Gresik Regency, East Java 61121. assisting other officers who handle administration in the Market Tax Sub-section, namely data processing Daily or monthly Market Tax payments still use a Tax Control Card or. To overcome this problem, an information system was developed using the PHP and HTML programming languages ​​and MYSQL DATABASE. The research methodology used in this research uses data collection methods. The conclusions are expected to help simplify the management of market services, such as managing traders, processing kiosks and losses, and processing fee data and reports, it is also hoped that it can reduce the risk of damage.